2014
DOI: 10.1097/ijg.0b013e31829484c6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Visual Field Progression Between Relatively Low and High Intraocular Pressure Groups in Normal Tension Glaucoma Patients

Abstract: Although progression rate was similar, the risk factors for VF progression were different in the 2 groups. These findings may suggest that IOP-dependent and IOP-independent factors affect VF progression differently in the 2 groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 55 publications
1
24
0
1
Order By: Relevance
“…In general, glaucoma progression was reported to accelerate in the middle stage and thereafter 16. In the present analysis using a Markov model, VFD aggravations in NTG were not conspicuous after the middle stage; instead, the progression seemed to be linear, as reported by Lee et al17 We conjectured that this observation may reflect an influence of medical therapy on the study subjects. We previously reported that the presence or absence of continuous aggravations of MD values was associated with long-term VFD during follow-up of NTG patients 18.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In general, glaucoma progression was reported to accelerate in the middle stage and thereafter 16. In the present analysis using a Markov model, VFD aggravations in NTG were not conspicuous after the middle stage; instead, the progression seemed to be linear, as reported by Lee et al17 We conjectured that this observation may reflect an influence of medical therapy on the study subjects. We previously reported that the presence or absence of continuous aggravations of MD values was associated with long-term VFD during follow-up of NTG patients 18.…”
Section: Discussionsupporting
confidence: 72%
“…VFD progression in NTG was reported to involve not only IOP factors, but also local factors, such as severity of myopia,23 central corneal thickness,24 and disc hemorrhage 15,17,24. While, disc hemorrhage has been considered as a significant risk factor, it is not a highly specific prognostic factor because it is difficult to detect every occurrence of disc hemorrhage in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Over four follow-up visits, each 6 months apart, the authors found no significant difference in either short-term or long-term IOP fluctuation between patients who progressed and those who remained stable. Lee et al 21 found comparable results in patients with NTG and at least 5 years of follow-up, reporting no significant association between SD in IOP and VF progression in univariate or multivariate analysis.…”
Section: Long-term Iop Fluctuationmentioning
confidence: 89%
“…In the group with pressure >15 mmHg, IOP was a risk factor for progression. However, in the group with lower pressures, the presence of optic disc hemorrhages was the only risk factor, demonstrating that progression mechanisms are not exclusively dependent on pressure values (84) . The risk factors for the progression of glaucomatous damage detected by the NTG Collaborative Study Group were female sex, mi graine, and occurrence of optic disc hemorrhage (85,86) .…”
Section: Visual Field Defects and Progressionmentioning
confidence: 99%